Malaria-diabetes comorbidity is linked to higher parasitaemia and enhanced IgG response to malaria vaccine candidate antigens - Gideon Agyare; David Courtin; Samuel Asamoah Sakyi; Gideon Kwesi Nakotey; Naa Adjeley Frempong; Prince Amoah Barnie; Samuel Kofi Tchum; Samuel Victor Nuvor; Benjamin Amoani (PLoS ONE, 2026)
Background The coexistence of type 2 diabetes mellitus (T2DM) and malaria presents a significant public health concern, particularly in malaria-endemic regions. T2DM’s immunomodulatory effects may influence immune responses to infectious diseases, but its impact on naturally acquired antibodies against malaria vaccine candidate antigens remains unclear. This study investigated how T2DM-malaria comorbidity affects IgG responses to malaria vaccine candidate antigens (GLURP-R2, GLURP-RO, MSP3, MSP1, AMA-1 and CSP) among individuals in the Central Region of Ghana. Methods This hospital-based case-control study recruited a total of 144 participants 40 with diabetes, 25 with both diabetes and malaria, 41 with malaria only, and 38 controls (hospital staff without malaria or diabetes matched by age and sex). Malaria status and parasitaemia were confirmed using microscopy, blood glucose levels were measured via glucometer, and antibody levels were quantified using indirect ELISA. Data were analyzed using parametric and non-parametric statistical methods. Results Patients with malaria-diabetes comorbidity exhibited significantly higher parasitaemia levels compared to those with malaria alone [1702 (IQR1 = 926.50, IQR3 = 4102) vs. 932 (IQR1 = 722.50, IQR3 = 1321), p = 0.02]. Relative to the negative control group, IgG responses to GLURP-R2 were markedly elevated, showing a 1.60-fold increase in the comorbidity group (β = 0.47 [95% CI: 0.10–0.83], p = 0.01) and a 1.43-fold increase in the malaria-only group (β = 0.36 [95% CI: 0.04–0.69], p = 0.03). Among individuals with comorbidity, IgG levels to GLURP-R0 and MSP1 were also 1.43-fold higher (β = 0.36 [95% CI: 0.03–0.68], p = 0.03) and 1.42-fold (β = 0.35 [95% CI: 0.09–0.61], p < 0.05), respectively. Conversely, antibody responses to MSP3, AMA1, and CSP did not differ significantly between the study groups (p > 0.05). In the multivariate regression model adjusted for age and sex, individuals with comorbidity exhibited significantly elevated IgG responses, showing a 1.38-fold increase to GLURP-R0 (β = 0.32 [95% CI: 0.07–0.59], p = 0.027) and a 1.34-fold higher response to MSP1 (β = 0.29 [95% CI: 0.02–0.47], p = 0.048), relative to the malaria-only group. Conclusion These findings suggest that diabetes may enhance malaria parasite multiplication while also augmenting IgG antibody responses to malaria vaccine candidate antigens in individuals with comorbidity. Further research is required to elucidate the mechanisms by which diabetes influences antibody responses to malaria infection and its potential implications for malaria vaccine development.